Corporate Social Responsibility dan Likuiditas terhadap Nilai Perusahaan dengan dimoderasi oleh Profitabilitas - Septiana, Gina; Rivandi, Muhammad (Yayasan Cita Cendikiawan Al Kharizmi, 2025)
This research aims to analyze the influence of Corporate Social Responsibility and liquidity on firm value and find out whether profitability can moderate it Corporate Social Responsibility and liquidity on firm value. This research uses Quantitative methodology using secondary data. Samples used in This research includes LQ45 companies that have been listed on the Indonesia Stock Exchange in 2020-2023. The sampling technique used was purposive sampling and A total of 18 companies have met the criteria as research samples. Analysis method used is panel regression. The research results show that Corporate Social Responsibility and liquidity have a positive and significant effect on firm value and Profitability moderates the negative relationship between Corporate Social Responsibility and liquidity on fim value.